1999
DOI: 10.1088/0029-5515/39/6/305
|View full text |Cite
|
Sign up to set email alerts
|

Density limits in TEXTOR-94 auxiliary heated discharges

Abstract: In a tokamak plasma the maximum achievable density is limited. A too high density will result in a violent end of a discharge. Two types of density limit disruption can be distinguished: (a) impure and moderately heated discharges, if the radiative power exceeds the input power, (b) clean, auxiliary heated discharges, where the Greenwald limit is encountered. It has been found that in TEXTOR-94 these two density limits differ by the radiative instability in the plasma boundary, which preceeds the disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
74
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 22 publications
11
74
0
Order By: Relevance
“…The reduction of the plasma contact with the wall at the HFS was balanced by a stronger impurity release from limiters at the low field side. 11 Recently, similar results have been obtained on JET. 14 By increasing the plasma wall clearance, the outflow of charged particles and energy to the inner wall is reduced and, consequently, the influx of recycling neutrals of the working gas and eroded impurities into the plasma is decreased.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The reduction of the plasma contact with the wall at the HFS was balanced by a stronger impurity release from limiters at the low field side. 11 Recently, similar results have been obtained on JET. 14 By increasing the plasma wall clearance, the outflow of charged particles and energy to the inner wall is reduced and, consequently, the influx of recycling neutrals of the working gas and eroded impurities into the plasma is decreased.…”
Section: Introductionsupporting
confidence: 72%
“…In limiter tokamaks, this ''wall'' MARFE normally leads to the density limit. [8][9][10][11] Recently, the wall MARFE was also observed in the divertor configuration in Joint European Torus ͑JET͒, where it occurs after the X-point MARFE and ultimately determines the maximum density in L-mode deuterium plasmas. 12 As demonstrated earlier, 7 unstable perturbations leading to the wall MARFE have their largest amplitude on the HFS.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the improved particle confinement phase exists for about 90 ms and the particle confinement time τ P increased about 1.6 times. The results are similar to the experiments in TFTR [13], and are consistent with the theoretical explanation [33] given for the TFTR results. The MARFE cools the plasma edge, and the electron density profile is observed to become more narrow and peaked.…”
Section: Discussionsupporting
confidence: 91%
“…It was evidence that the critical value of n e (0.7a)Z e f f in the MARFE onset always correlated with the total input power which has been observed in the FTU [12] and the HT-7 limiter tokamak [7][8], here n e (0.7a) is the line average density, measured at the outermost interferometer channel at r =20 cm (r =0.7a, the minor radius a = 27∼28 cm). In the TEXTOR-94, dependence of the edge electron density (r = a + 1 cm) on the heating power was also observed [13]. Therefore, it suggests experimentally the importance of impurity radiation and localized power balance in the MARFE formation.…”
Section: Introductionmentioning
confidence: 69%
“…values close to the operational limit of TEXTOR-94 (b n ഠ 2) for the typical RI-mode conditions [10]. The key factor to obtain these results is appropriate tailoring of the deuterium gas fueling in addition to (i) careful wall conditioning (in this case fresh siliconization) and a proper positioning of the discharge with respect to the limiters, leading to conditions which avoid multifaceted radiation from the edge (MARFE) formation at high density by reducing the recycling at the inner wall [11], and (ii) edge radiation cooling (in this case due to sputtering of Si), these two last conditions being necessary for high confinement radiative mantle discharges in TEXTOR. Similar results are found in discharges with additional neon seeding to produce the radiative belt under boronized or siliconized wall conditions.…”
mentioning
confidence: 99%